Acheloios, Thales, and the origin of philosophy : a response to the neo-Marxians - Molinari, Nicholas J., (Archaeology and classical humanities ;, 2022)
Through careful analysis of the archaeological record, close reading of ancient sources, and deep investigations into the languages of our past, this study demonstrates the importance of the influence of the cult of Acheloios on Thales, fundamentally changing our understanding of the origin of the philosophical experience in 6th century Ionia.